2022
DOI: 10.1002/chem.202104376
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Influence of Donor‐Acceptor Diazo Compounds on the Catalyst Efficiency of B(C6F5)3 Towards Carbene Formation

Abstract: Diazo compounds have been largely used as carbene precursors for carbene transfer reactions in a variety of functionalization reactions. However, the ease of carbene generation from the corresponding diazo compounds depends upon the electron donating/withdrawing substituents either side of the diazo functionality. These groups strongly impact the ease of N2 release. Recently, tris(pentafluorophenyl)borane [B(C6F5)3] has been shown to be an alternative transition metal‐free catalyst for carbene transfer reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…To clarify the advantages of the activation mode with the B−C bond over the B−O mode, 59 contrary to the reported reaction system, we performed further mechanistic studies. We analyzed the two transition states TS2 B-O and TS2 B-C because these saddle points decide which to generate Lewis acid-activated carbene (2) or atypical carbene−borane complex (6) (Figure 1c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To clarify the advantages of the activation mode with the B−C bond over the B−O mode, 59 contrary to the reported reaction system, we performed further mechanistic studies. We analyzed the two transition states TS2 B-O and TS2 B-C because these saddle points decide which to generate Lewis acid-activated carbene (2) or atypical carbene−borane complex (6) (Figure 1c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This also indicates the substitution effect present at the aryl ring of diazoester toward cyclopropanation. Furthermore, Ariafard 25 pointed out that the stronger π-donor the para substituent of the aryl ring, the more efficient the B(C 6 F 5 ) 3 catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…of the diazo ester (Figure 1b ). 35 The calculations showed that there is a strong correlation between the reaction free energy of carbene formation and the activation barrier to N 2 release. Thus, generally there was a lower activation barrier to the process when a more stable carbene is generated.…”
Section: Diazo Activation Using Catalytic B(c 6 F ...mentioning
confidence: 98%
“…This was found both experimentally and computationally (Figure 1 ). 31 34 35 By DFT studies the C–N bond in the boron-coordinated diazo ester is longer and weaker (1.334 Å) than in the free uncoordinated diazo ester (1.318 Å). 14 In addition, a shortening of the C–C bond length from 1.470 Å to 1.436 Å was also observed for the O→B adduct.…”
Section: Diazo Activation Using Catalytic B(c 6 F ...mentioning
confidence: 99%